Macronutrient absorption rate of a Runner-type peanut cultivar - Bertino, Antonio M. P. [UNESP]; de Faria, Rogerio T. [UNESP]; Jesus, Eduardo da S. B. [UNESP]; Alves, Thayane L. [UNESP]; Cazuza Neto, Ancelmo [UNESP]; Barbosa, José de A. [UNESP] (FapUNIFESP (SciELO), 2022)
Peanuts are one of the most produced legumes in the world; however, there is a lack of knowledge on their nutritional needs and the growth phases with greater demands; therefore research is required on the nutrient absorption rate of the crop. The objectives of this study were to determine the rates of absorption in the vegetative part and the pods, the accumulation of macronutrients in the vegetative part, pods, and in total, and the nutrient export to pods during the cycle of the peanut, cv Runner IAC 503, grown under full irrigation. The experiment was conducted at the Experimental Farm of the Faculty of Agrarian and Veterinary Sciences, Universidade Estadual Paulista, Jaboticabal campus, SP, Brazil, from March to August 2019 using a randomized block design, with evaluations of the macronutrient absorption rate and accumulation at 35, 49, 63, 77, 91, 105, 119, 133 and 147 days after sowing, with four replications. Higher nutritional demands of peanuts occurred between 63 and 105 days after sowing. Greater total accumulation of nutrients was reached at 118 DAS, with 234.8, 173.5, 79.0, 45.8, 23.4 and 18.8 kg ha-1 for N, K, Ca, Mg, P, and S, respectively. Exports of macronutrients contained in the pods totaled 138.8, 43.9, 14.6, 12.0, 7.3 and 5.4 kg ha-1 for N, K, P, Mg, S and Ca, respectively. Exported K in the harvest was two times greater than the applied amount at sowing, which followed the current Brazilian recommendation, causing possible depletion of this nutrient in the soil.
Marcha de absorção de macronutrientes de uma cultivar de amendoinzeiro do tipo Runner
Keywords: Arachis hypogaea L; Nutrients; Nutritional demand